Genetic Deletion of Akt3 Induces an Endophenotype Reminiscent of Psychiatric Manifestations in Mice - Bergeron, Yan; Bureau, Geneviève; Laurier-Laurin, Marie-Élaine; Asselin, Eric; Massicotte, Guy; Cyr, Michel (Frontiers in Molecular Neuroscience, 2017)
The protein kinase B (PKB/Akt), found in three distinctive isoforms (PKBα/Akt1, PKBβ/Akt2, PKBγ/Akt3), is implicated in a variety of cellular processes such as cell development, growth and survival. Although Akt3 is the most expressed isoform in the brain, its role in cerebral functions is still unclear. In the present study, we investigated the behavioral, electrophysiological and biochemical consequences of Akt3 deletion in mice. Motor abilities, spatial navigation, recognition memory and LTP are intact in the Akt3 knockout (KO) mice. However, the prepulse inhibition, three-chamber social, forced swim, tail suspension, open field, elevated plus maze and light-dark transition tests revealed an endophenotype reminiscent of psychiatric manifestations such as schizophrenia, anxiety and depression. Biochemical investigations revealed that Akt3 deletion was associated with reduced levels of phosphorylated GSK3α/β at serine 21/9 in several brain regions, although Akt1 and Akt2 levels were unaffected. Notably, chronic administration of lithium, a mood stabilizer, restored the decreased phosphorylated GSK3α/β levels and rescued the depressive and anxiety-like behaviors in the Akt3 KO mice. Collectively, our data suggest that Akt3 might be a critical molecule underlying psychiatric-related behaviors in mice.